Zeolite Application Improves Soil Structure and Water Retention in Agriculture: Aplikasi Zeolit Memperbaiki Struktur Tanah dan Retensi Air di Bidang Pertanian - Jabbar, Hadeel Amer (Academia Open, 2025)
General Background: Sustainable agriculture increasingly relies on soil amendments that improve physical properties and resource efficiency. Specific Background: Zeolites—hydrated crystalline aluminosilicates—are recognized for their high porosity, cation exchange capacity, and water retention, making them valuable in soil management. Knowledge Gap: Despite broad applications, a comprehensive understanding of zeolite's role in enhancing physical soil properties across various textures under field conditions remains limited. Aims: This review investigates zeolite’s influence on soil bulk density, porosity, water retention, and overall plant productivity, particularly under water stress. Results: Findings from multiple field and laboratory studies reveal that zeolite addition improves water-holding capacity, reduces soil bulk density, enhances total porosity, and increases crop yield and water use efficiency. Novelty: The synthesis of recent evidence demonstrates that zeolites not only act as soil conditioners but also serve as strategic tools in mitigating water stress and optimizing nutrient use, outperforming other soil amendments such as biochar under similar conditions. Implications: These insights support integrating zeolite into sustainable soil management practices to bolster agricultural resilience in arid and semi-arid environments, aligning with global efforts toward resource-efficient and climate-adaptive farming systems. Highlight : Water Use Efficiency: Zeolites improve soil's ability to retain water, significantly benefiting crops under drought or limited irrigation. Soil Structure Enhancement: They reduce bulk density and increase porosity, enhancing root growth and nutrient movement. Nutrient Management: Zeolites act as slow-release reservoirs, increasing nutrient availability while minimizing leaching. Keywords : Zeolites, Soil Conditioner, Water Retention, Nutrient Efficiency, Sustainable Agriculture